2000
DOI: 10.1111/j.1532-849x.2000.00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of cement microfracture under crowns using 3D‐FEA

Abstract: Although the chamfer margin design could lead to greater stresses near the margins that places the cement at risk for microfracture and possible crown failure, glass-ionomer and composite resin cements have more favorable mechanical properties for resisting microfracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 22 publications
4
17
0
Order By: Relevance
“…However, no significant changes were observed between cement thicknesses of 30 μm and 50 μm. Thus, cement thickness had minimal effect on maximum principal stress, as was shown in previous studies 17,18) . This minimal effect could be due to the approximate elasticity values of cement (8 MPa) and dentin (16 MPa).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…However, no significant changes were observed between cement thicknesses of 30 μm and 50 μm. Thus, cement thickness had minimal effect on maximum principal stress, as was shown in previous studies 17,18) . This minimal effect could be due to the approximate elasticity values of cement (8 MPa) and dentin (16 MPa).…”
Section: Discussionsupporting
confidence: 53%
“…This minimal effect could be due to the approximate elasticity values of cement (8 MPa) and dentin (16 MPa). It was reported that cements transfer stresses to dentin with the elastic moduli and thicknesses of cement, core and supporting materials playing a significant role 17,18) . Results of the present study indicated that the core material played a determinant role on stress transfer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a "mold" to enclose a specimen could in theory distribute the point load of a 0.2-mm blunt shear knife around the mold in order to minimize any concentrated shear stresses associated with a shear knife being placed directly onto a specimen. For this µSBS method, a full FEA analysis on the mold-enclosed µSBS method would be required to be performed in order to establish this and comparisons made with other studies 17,20,28,29) . Furthermore, the use of a mold-enclosed specimen format eliminates the requirement to remove the specimen from the mold, potentially reducing the amount of pre-test failures observed when separating µSBS specimens from a mold for non-enclosed specimens.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that the cement thickness minimally affected stress levels and distributions and greater stresses were found in cements with the greater Young's modulus [28].…”
Section: Introductionmentioning
confidence: 98%